Impact of Service Quality on Customer Satisfaction in Telecom Sector of Pakistan - Muhammad Majid Mahmood Bagram, Rehmat Ullah & Salman Farooq (JCMS, 2023)
The purpose of this research paper is to investigate the important factors that link with customer satisfaction in telecom sector of Pakistan, which are in the form of service quality and customer satisfaction. A research field was conducted. The questionnaire was taken from existing constructs in the relevant field. The majority of respondent belong to non-business mobile users of Pakistan. Answer of the research questions were tested through reliability test and statistical analysis. The service quality dimensions namely billing system, pricing structure and customer services have positive significant influence on customer satisfaction. Future study could examine inertia, trust and the attractiveness of alternatives. Moreover, future research can take place as the mediating role of possible switching costs and the inter link between services quality and customer satisfaction. The drives of the customer satisfaction in Telecom sector are very important for mobile operators. The present research is very useful for managers of Telecom sector company to implement the customer satisfaction strategies to improve their business and profit level.